2004
DOI: 10.1038/sj.bdj.4811225
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo assessment of a glass slow fluoride releasing device: a pilot study

Abstract: AimsThe aims were to evaluate a) whether a slow release fluorideglass pellet (SFG) would be retained in the mouth and release fluoride (F) over a long period of time, b) what concentrations of F in the glass would provide ideal intra-oral saliva F concentrations and c) whether an SFG would affect blood plasma concentrations of F after swallowing compared with ingestion of a commercial NaF tablet. Methods a) A prototype SFG was attached to a maxillary molar of a volunteer. Baseline saliva F concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
(18 reference statements)
1
13
0
6
Order By: Relevance
“…Since its invention in 1984, several studies were conducted to evaluate the clinical effect, cost effectiveness and safety of the FSSRD. 10 Toumba 11 studied the FSSRD extensively both in vivo and in vitro and concluded that (a) the mean salivary fluoride (F) level with a device containing 13.3% F in human volunteers was elevated to 0.17 ppm compared with 0.01 ppm over a period of one month, 12 (b) the FSSRD posed no risk of F toxicity, since ingesting this device showed no alteration to plasma baseline F levels, 12,13 (c) using an in situ intra-oral model, it was demonstrated that F could exert an equal effect on the remineralisation of enamel slabs on both sides of the oral cavity, indicating that F had distributed to the opposite side of the oral cavity from a single FSSRD, 11 (d) a double blind randomised clinical caries trial, with high caries-risk children showed significantly fewer carious teeth for the F device, than the control (placebo) device group, over a two year period. For dmft-DMFT there were 67% fewer new carious teeth and for dmfs-DMFS there were 76% fewer new carious surfaces, 13,14 and (e) FSSRDs were shown to have very favourable cost-benefit and cost-effectiveness ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Since its invention in 1984, several studies were conducted to evaluate the clinical effect, cost effectiveness and safety of the FSSRD. 10 Toumba 11 studied the FSSRD extensively both in vivo and in vitro and concluded that (a) the mean salivary fluoride (F) level with a device containing 13.3% F in human volunteers was elevated to 0.17 ppm compared with 0.01 ppm over a period of one month, 12 (b) the FSSRD posed no risk of F toxicity, since ingesting this device showed no alteration to plasma baseline F levels, 12,13 (c) using an in situ intra-oral model, it was demonstrated that F could exert an equal effect on the remineralisation of enamel slabs on both sides of the oral cavity, indicating that F had distributed to the opposite side of the oral cavity from a single FSSRD, 11 (d) a double blind randomised clinical caries trial, with high caries-risk children showed significantly fewer carious teeth for the F device, than the control (placebo) device group, over a two year period. For dmft-DMFT there were 67% fewer new carious teeth and for dmfs-DMFS there were 76% fewer new carious surfaces, 13,14 and (e) FSSRDs were shown to have very favourable cost-benefit and cost-effectiveness ratios.…”
Section: Introductionmentioning
confidence: 99%
“…13 Slow-release fluoride beads bonded onto teeth to help prevent cavities have also been shown to have a beneficial effect in reducing sensitivity. 14 The aim of the present study is to investigate the feasibility of physically blocking dentinal tubules by using nanoparticles of hydroxyapatite (nHAp). The premise is that if nHAp enter the exposed tubules, they may act as a scaffold for tissue growth and promote mineralisation reactions which effectively, and permanently, seal the tubules, thereby preventing sensitivity problems.…”
Section: Introductionmentioning
confidence: 99%
“…We don't know, for example, if an episode of acute toxicity might develop if a child accidentally swallows a dislodged SFG. In a previously published article, 7 which is referenced in the text of the reviewed paper, the authors reported that the ingestion of an SFG produced no increase in blood plasma F concentration throughout a 3-hour postingestion period. Nevertheless, it should be noticed that this conclusion was drawn from studying 5 adult volunteers.…”
Section: Commentary and Analysismentioning
confidence: 99%